Comments on the 2016 Award of APS Medal for Exceptional Achievement in Research: --a big step backward in physics of APS (JOURNAL OF ADVANCES IN PHYSICS, 2016)
The 2016 APS (American Physical Society) Medal for Exceptional Achievement in Research awarded to E. Witten for discoveries in the mathematical structure of quantum field theory, is indeed exceptional because there is no experimental support. This would be a big step backward from Galileo's experimental-based tradition. Moreover, the Selection Committee of APS was unaware that Witten does not understand general relativity and actually has made mathematical and physical mistakes that leads to the errors on general relativity in the press release of the 1993 Nobel Committee for Physics. However, an unexpected benefit of this award is that it leads to the exposition on the shortcomings in mathematics and physics of APS.